The Effectiveness of Artificial Reefs in Improving Ecosystem Health to Increase Coral Reef Resilience - Reny Puspasari; Ngurah Nyoman Wiadnyana; Sri Turni Hartati; Rita Rachmawati; Yunaldi Yahya (Pusat Riset Kelautan, 2020)
Some coral bleaching phenomena related to climate variability (ENSO or IOD) lead to coral mortality resulting in ecosystem damage and decreased ecosystem health. The artificial reef is one of the management efforts adopted by stakeholders to restore coral reef conditions. Thriving artificial reefs could extend coral coverage and provide a new habitat for several marine organisms and divert anthropogenic pressure on natural coral ecosystems. The current research aims to identify the impact of artificial reef installment on ecosystems and fisheries. Three indicators for health coral reef ecosystems were determined: increased coral cover, biofouling organism, and fish abundance and diversity. An index to measure the artificial reef impacts on fisheries is fish production after installment. Data collection was done in 2017 in around Bali area, including the occurrence of coral bleaching, the number of artificial reefs installed, and the case of positive impacts of artificial reefs. The data were analyzed to measure any changes that occurred after the artificial reef installment. The results show that an artificial reef installment has a significant impact on increasing coral cover, fouling organisms, and fish abundance and species richness. The new community structure development varies among the artificial reef depend on the environmental condition. However, the impact of artificial reef installment could not be directly quantified on fish production due to unavailability monitoring data.